Supine Imaging Is a Superior Predictor of Long-Term Alignment Following Adult Spinal Deformity Surgery. Issue 4 (May 2022) - Elysee, Jonathan Charles; Lovecchio, Francis; Lafage, Renaud; Ang, Bryan; Huang, Alex; Bannwarth, Mathieu; Kim, Han Jo; Schwab, Frank; Lafage, Virginie
Study Design: Retrospective cohort study. Objective: To investigate correlations between preoperative supine imaging and postoperative alignment. Methods: A retrospective review was conducted of a single-institution database of patients with adult spinal deformity (ASD). Patients were stratified by fusion location in the lumbar or thoracic spine. Outcomes of interest were postoperative lumbar lordosis (LL) and thoracic kyphosis (TK). Sagittal alignment parameters were compared and correlation analyses were performed. Multilinear stepwise regression was conducted to identify independent predictors of postoperative LL or TK. Regression analyses were repeated within the lumbar and thoracic fusion cohorts. Results: A total of 99 patients were included (mean age 63.2 years, 83.1% female, mean body mass index 27.3 kg/m 2 ). Scoliosis Research Society classification demonstrated moderate to severe sagittal and/or coronal deformity (pelvic tile modifier, 18.2% ++; sagittal vertical axis, 27.3% ++, pelvic incidence minus lumbar lordosis mismatch, 29.3% ++, SRS type, 29.3% N type curve and 68.7% L or D type curve). A total of 73 patients (73.7%) underwent lumbar fusion and 50 (50.5%) underwent thoracic fusion. Correlation analyses demonstrated a significant association between pre- and postoperative LL and TK. Multilinear regression demonstrated that LL supine and pelvic incidence were significant predictors of postoperative LL ( r 2 = 0.568, P < .001). LL supine, TK supine, and age were significant predictors of postoperative TK ( r 2 = 0.490, P < .001). Conclusion: Preoperative supine films are superior to standing in predicting postoperative alignment at 1-year follow-up. Anticipation of undesired alignment changes through supine imaging may be useful in mitigating the risk of iatrogenic malalignment.